Estudo de irregularidades de superfície das pistas de pouso de dois aeródromos militares - Cardoso, Samuel Hanthequeste (1982)
Interaction airplane-pavement and criteria for pavement surface unevenness evaluation is presented. An initial study with the BPR roughmeter in two Military Aerodrommes is presented. Topographic levelling of points one meter from each other and data analysis either through drafted profiles and special template or using a statistical approuch. These procedures permit to detect areas of excessive irregularities and the transition areas to those of acceptable unevenness, in connection with pilot’s experience.